Disparities in hypertension among black Caribbean populations: a scoping review by the U.S. Caribbean Alliance for Health Disparities Research Group (USCAHDR). Issue 1 (December 2015) - Bidulescu, Aurelian; Francis, Damian; Ferguson, Trevor; Bennett, Nadia; Hennis, Anselm; Wilks, Rainford; Harris, Eon; MacLeish, Marlene; Sullivan, Louis
Abstract Background Despite the large body of research on racial/ethnic disparities in health, there are limited data on health disparities in Caribbean-origin populations. This scoping review aimed to analyze and synthesize published and unpublished literature on the disparities in hypertension and its complications among Afro-Caribbean populations. Methods A comprehensive protocol, including a thorough search strategy, was developed and used to identify potentially relevant studies. Identified studies were then screened for eligibility using pre-specified inclusion/exclusion criteria. An extraction form was developed to chart data and collate study characteristics including methods and main findings. Charted information was tagged by disparity indicators and thematic analysis performed. Disparity indicators evaluated include ethnicity, sex, socioeconomic status, disability, sexual orientation and geographic location. Gaps in the literature were identified and extrapolated into a gap map. Results A total of 455 hypertension related records, published between 1972 and 2012, were identified and screened. Twenty-one studies met inclusion criteria for detailed analysis. The majority of studies were conducted in the United Kingdom and utilized a cross-sectional study design. Overall, studies reported a higher prevalence of hypertension among Caribbean blacks compared to West African blacks and Caucasians. Hypertension and its related complications were highest in persons with low socioeconomic status. Gap analysis showed limited research data reporting hypertension incidence by sex and socioeconomic status. No literature was found on disability status or sexual orientation as it relates to hypertension. Prevalence and morbidity were the most frequently reported outcomes. Conclusion The literature on hypertension health disparities in Caribbean origin populations is limited. Future research should address these knowledge gaps and develop approaches to reduce them.